2013
DOI: 10.2320/matertrans.mh201312
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures of Pearlite and Martensite Transformed from Ultrafine-Grained Austenite Fabricated through Cyclic Heat Treatment in Medium Carbon Steels

Abstract: This study investigated the microstructures of pearlite and martensite transformed from ultrafine-grained austenite in 0.45C steel and Vadded 0.45C steel. The mean prior austenite grain sizes were refined to be 4.5 µm in the 0.45C specimen and 2.4 µm in the V-added 0.45C specimen through cyclic heat treatment of austenitizing and water quenching, i.e., repetition of martensite § austenite transformations. The austenite with various grain sizes was either air-cooled or water-quenched to cause pearlitic or marte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Instead of the typical lamellar pearlite, the specimen showed the pearlite structures composed of fragmented cementite dispersed in ferrite, as was indicated by the arrow in Figure 8F. Shibata et al (2013) also observed such a pearlite structure in a medium-carbon steel and explained the formation of fragmented pearlite transformed from fine-grained austenite in the following way. When the austenite grain size is smaller, the distance between neighboring pearlite colonies formed on austenite grain boundaries (or triple junctions of austenite grain boundaries) becomes shorter.…”
Section: Grain Refinement Of Ferrite + Pearlite Microstructuresmentioning
confidence: 75%
See 1 more Smart Citation
“…Instead of the typical lamellar pearlite, the specimen showed the pearlite structures composed of fragmented cementite dispersed in ferrite, as was indicated by the arrow in Figure 8F. Shibata et al (2013) also observed such a pearlite structure in a medium-carbon steel and explained the formation of fragmented pearlite transformed from fine-grained austenite in the following way. When the austenite grain size is smaller, the distance between neighboring pearlite colonies formed on austenite grain boundaries (or triple junctions of austenite grain boundaries) becomes shorter.…”
Section: Grain Refinement Of Ferrite + Pearlite Microstructuresmentioning
confidence: 75%
“…On the other hand, an alternative way utilizing cyclic transformation between martensite and austenite was established by Grange to make austenite grain sizes in steels smaller than 1-2 μm without deformation (Grange, 1971). Shibata et al (2013) used the cyclic heat treatment for refining austenite grain sizes in medium carbon steels and could obtain the austenite grain size of 4.5 and 2.4 μm in a 0.44C-0.86Mn (mass %) steel and a 0.46C-0.84Mn-0.3V steel, respectively. Furuhara et al (2008) used a cyclic heat treatment followed by air-cooling and reported that fine-grained ferrite having a grain size of 2.2 μm was successfully obtained in a medium-carbon steel with a chemical composition of Fe-0.35C-1.05Cr-0.17Mo (in mass%).…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the purpose of adding microalloying elements into the traditional chemical composition system of hot-stamped steel (e.g., 22MnB5 and 30MnB5) is to reduce the size of austenite and enhance the strength of matrix before martensitic transformation, and a fine martensitic lath will be obtained ultimately after hot-stamping process [15][16][17][18][19]. Compared with V free hot-stamped steel, the vanadium microalloying element is introduced in 30MnBNb hot-stamped steel, the susceptibility to HE and the microstructures are analyzed, and the results are summarized in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…However, it seems difficult to apply SPD processes to mass production of steels because of the limited dimensions of the SPD processed materials. Several alternative processes for refining grain size other than SPD have been also proposed, for example, repetitive heat treatment [12,13] and recrystallization of cold-rolled DP steel [14]. In the present study, grain refinement of ferrite and DP structures through repetitive heat treatment and subsequent cold-rolling and recrystallization was investigated.…”
Section: Introductionmentioning
confidence: 99%